PENGARUH METODE ABJAD BERBANTUAN MEDIA GAMBAR TUNGGAL DALAM MENINGKATKAN KETERAMPILAN MENULIS PERMULAAN PESERTA DIDIK FASE A SEKOLAH DASAR - Risyda Khoerunnisa; N.Tatat Hartati; Evi Rahmawati (STKIP Subang, 2025)
This study was motivated by the problem of the uneven writing skills of grade 1 students, namely students who still have difficulty writing letters properly, even though letter writing skills are one of the basic skills that students must master to support other science learning. This study aims to describe the effect of the alphabet method assisted by single image media in improving the initial writing skills of phase A elementary school students. The method used is a quantitative method (quasi-experiment) with the form of a non-equivalent control group design. The population in this study was phase A grade 1 learners in one of the public elementary schools in Tasikmalaya Regency. The sample of this study involved 25 students in the control class and 25 students in the experimental class. The results of the data analysis showed the value of Asymp. Sig. (2-tailed) value of 0.002 (0.002 < 0.005), which indicates a significant effect of the alphabet method assisted by single-picture media in improving students' beginning writing skills. Thus, the alphabetic method assisted by single image media is worth considering to be applied in learning beginning writing in phase A elementary school students.